Feeding habits of Aspitrigla cuculus (L., 1758) (red gurnard), Lepidotrigla cavillone (Lac., 1802) (large scale gurnard) and Trigloporus lastoviza (Brunn., 1768) (rock gurnard) around Cyclades and Dodecanese Islands (E. Mediterranean) - TERRATS, A.; PETRAKIS, G.; PAPACONSTANTINOU, C. (Mediterranean Marine Science, 2000)
The feeding habits of the three most abundant gurnard species, red gurnard (Aspitrigla cuculus), large scale gurnard (Lepidotrigla cavillone) and rock gurnard (Trigloporus lastoviza) in the eastern Mediterranean (Dodecanese and Cyclades, Greece) are examined. The stomach contents of the gurnard specimens collected in April and September 1996 by bottom trawling were analyzed. The % frequency of occurrence, % number and % weight of prey types in the stomach contents were evaluated. By weight, Mysidacea and Decapoda dominated in the diet of the three species in both seasons, however the Index of Relative Importance, as well as the percentage frequency of occurrence varied. Rock gurnard presented the most diverse diet whereas the diet of large scale and red gurnard were more specialized. High overlap in terms of number was found between rock and large scale gurnard in May. Rock gurnard had the most divers diet in both seasons.